PENTINGNYA TEOLOGI DI ABAD 21 - Lumintang, Ramly Donald Belly (Didache: Jurnal Teologi dan Pendidikan Kristen, 2025)
This article explains the importance of theology in the 21st century which is able to answer academic needs as a way to answer the challenges of this century. Theology comes in three perspectives, namely theology from above, theology from below and incarnational theology. The author's offer is through incarnational theology which emphasizes that the incarnation of Christ is a theological model that is very capable of answering the challenges of doing theology and church today in the 21st century. Artikel ini menjelaskan mengenai pentingnya Teologi di abad 21 yang mampu menjawab kebutuhan akademis sebagai jalan menjawab tantangan di abad ini. Teologi hadir dalam tiga perspektif yaitu teologi from above, from bellow dan teologi inkarnasional. Tawaran penulis melalui teologi inkarnasional yang menegaskan bahwa inkarnasi Kristus sebagai model teologi yang sangat mumpuni menjawab tantangan berteologi dan bergereja pada masa kini diabad 21.